Finite element analysis of reinforced concrete curved box-girder bridges - Preeti Agarwal; Priyaranjan Pal; Pradeep Kumar Mehta (Advances in Bridge Engineering, 2023)
Abstract The study presents the design forces of simply supported single-cell reinforced concrete (RC) curved box-girder bridges using a finite element method (FEM) based CSiBridge v.20 software. An existing model has been used to validate the present modelling approach. Models subjected to vertical loading, i.e., dead load (DL) and Indian road congress live load (LL), are considered for investigation. An intensive parametric study examines the maximum values of bending moment (BM), shear force (SF), torsional moment (TM), and vertical deflection (VD) in both girders of bridges. The influences of curve angle and span are considered in the study. The effect of curve angle, up to 12°, is negligible on forces and deflections, and thus such bridges can be analysed as a straight one. Finally, non-dimensional equations are derived for evaluating forces and deflections, so that one may predict these quantities for curved bridges based on straight bridge’s results. Engineers and designers may consider present work valuable in analysing, and designing curved box-girder bridges.